Modeling of Automatic Door at Railroad Crossing Without Guard Based on Internet of Things in Indonesia - Daniel Limantara, Arthur; Nisa, Vegyta Fakhrun; Gardjito, Edy; Subiyanto, Bambang; Nursandah, Fauzie; Sudarmanto, Hery Lilik; Limantara, Vincentius Arthur; Prayogo, Devin; Situmorang, Adolf; Mudjanarko, Sri Wiwoho (International Journal of Integrated Engineering, 2020)
Railroad crossings without doors and guarding are the cause of accidents between vehicles with trains other than human factors, and in Java, Indonesia has 6,000 level crossings. The solution that can be done is to install a door, but if a door is installed, a guard is needed to operate the door, this will cause new problems, namely employment. So the right solution is to design an automatic door, this study aims to create a sensor-based automatic door model and Internet of Things (IoT). The design of a miniature model of automatic railroad doorstop using SG90 9g micro servo with TCRT-5000 sensor based on Arduino Uno ATmega 328 microcontroller. The sensor is used to detect the position of the train, in miniatures that have been made using 2 TCRT-5000 sensors. The function of each sensor is to detect the arrival of the train, activate the speed and detection system that the train has passed through the doorstop. Miniature door bars are driven by 9g SG90 micro servo. Computer monitors in miniatures can function properly, which is capable of displaying train speed and waiting time for train arrival. The results of the miniature performance test for all supporting components can function optimally, namely the TCRT-5000 sensor can function and be accurate in detecting the position of the train and servo that move according to the miniature system program.